Learning Engagement as the Primary Catalyst for Transforming Social Support into Rural Teaching Commitment Among Prospective Teachers - Muhammad Fahmi Johan Syah; Miftakhul Huda; Arief Cahyo Utomo; Gallant Karunia Assidik; Mahaliza Mansor; Hanifah Tria Intan Jelita; Alifa Salsabila; Salma Rahmadhani Puspita Sari (Jurnal Pendidikan Progresif, 2026)
This study aims to analyze the prediction of social support role on rural teaching commitment (RTC), with learning engagement as a mediator. The study involved 350 prospective teachers at the undergraduate and professional teacher education (PPG) levels in Indonesia. Data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. The results showed that the majority of respondents had moderate levels of social support, learning engagement, and RTC. Specific findings indicate that emotional support is the most fundamental social support item in forming engagement. The PLS-SEM analysis confirmed the prediction that learning engagement functions as a strong partial mediator. Although social support contributes directly to teaching commitment in remote areas, its influence becomes even more significant when mediated by learning engagement, namely vigor, dedication, and absorption. However, the current RTC component remains dominated by the normative aspect (obligation), indicating a risk of low teacher retention. This study concludes that teacher placement policies cannot rely solely on administrative and normative approaches; they must integrate strengthening the basic capital within prospective teachers with a conducive school and community environment to create a sustainable commitment in rural areas of Indonesia. Furthermore, this study highlights the need for curriculum reform in both undergraduate teacher education and professional teacher education programs. These curricula should be deliberately designed to internalize key dimensions such as social support, learning engagement, and long-term teaching commitment. This can be achieved by integrating structured learning experiences, including community-based teaching practices, reflective activities, mentoring systems, and immersion programs in rural contexts. Such initiatives are expected to not only enhance prospective teachers’ adaptive capacities but also strengthen their emotional attachment, sense of purpose, and resilience in undertaking teaching assignments in underserved areas. Keywords: learning engagement, social support, rural teaching commitment, pre-service teacher, PLS-SEM.